INOVASI PROGRAM SI NDUK (SISTEM INFORMASI ONLINE DOKUMEN KEPENDUDUKAN) PADA DINAS KEPENDUDUKAN DAN CATATAN SIPIL KABUPATEN BOJONEGORO - Reskhy Illhami Eka Putri; Eva Hany Fanida (Publika, 2021)
In Indonesia, the first positive case finding for Covid-19 was in March 2020. This requires the central government to take policies to reduce the number of transmission of the Covid-19 virus. In addition, the existence of this pandemic requires limitations in public services. So that the government, which is Bojonegoro Regency Population and Civil Registry Office makes public service innovations to reduce crowd numbers and also improve the quality of population administration services. The innovation is Si Nduk Application (Online Population Document Information System). The purpose of this study was to find out how the implementation of the Si Nduk Program (Online Population Document Information System )by Bojonegoro Regency Population and Civil Registry Office . The data collection technique used is descriptive qualitative, while the focus of research in this study is based on the theory of innovation success attributes according to Bugge at al (2018). The result of this research is that the Si Nduk program has a legal basis based on the Regent's Circular No. 800/2862/414.202/2012 concerning the Implementation of Emergency PPKM in Bojonegoro Regency where its implementation is under the field of Population Administration Information Management. The source of the idea for this innovation is the Covid-19 pandemic, so that the government is expected to make more practical public service innovations. The culture of innovation in the Si Nduk application is that applicants register by entering their NIK and KK, then upload the required documents and wait for the file collection schedule. Then take the necessary files according to the location and time listed, and don't forget to bring the physical file requirements that have been uploaded. regarding the cost of population administration services through Si Nduk does not charge any fees, while the obstacles in implementing this program are network and socialization issues that need to be improved. Keywords: Covid-19, Service, Population Administration, Si Nduk Di Indonesia temuan kasus positif Covid-19 pertama yaitu pada bulan Maret 2020. Hal ini mengharuskan pemerintah pusat untuk mengambil kebijakan guna menekan angka penularan virus Covid-19. Sehingga pihak pemerintah salah satunya Dinas Kependudukan dan Catatan Sipil Kabupaten Bojonegoro membuat inovasi pelayanan publik guna menekan angka kerumunan dan meningkatkan kualitas pelayanan administrasi kependudukan. Inovasi yang dilakukan adalah meluncurkan Aplikasi Si Nduk. Tujuan dari penelitian ini adalah untuk mengetahui bagaimana pelaksanaan Inovasi Program Si Nduk (Sistem Informasi Online Dokumen Kependudukan) pada Dinas Kependudukan dan Catatan Sipil Kabupaten Bojonegoro. Teknik pengumpulan data yang digunakan adalah deskriptif kualitatif sedangkan fokus penelitian dalam penelitian ini adalah berdasarkan pada Teori Atribut Keberhasilan Inovasi menurut Bugge at al., (2018). Hasil dari penelitian ini adalah program Si Nduk berlandasan hukum berdasarkan Surat Edaran Bupati nomor 800/2862/414.202/2012 Tentang Pemberlakuan PPKM Darurat di Kabupaten Bojonegoro dimana pelaksanaannya dibawah bidang Pengelolaan Informasi Administrasi Kependudukan. Sumber ide untuk inovasi ini adalah adanya pandemi covid-19 sehingga membuat pemerintah diharapkan dapat membuat inovasi pelayanan publik yang lebih praktis. Budaya inovasi dalam aplikasi Si Nduk adalah para pemohon melakukan registrasi dengan memasukan NIK dan KK, kemudian meng-upload berkas persyaratan dan menunggu jadwal pengambilan berkas. Kemudian mengambil berkas yang diperlukan sesuai dengan lokasi dan waktu yang tertera, dan membawa berkas persyaratan yang telah di upload. Untuk biaya pelayanan administrasi kependudukan melalui Si Nduk tidak memungut biaya apapun sedangkan hambatan dalam pelaksanaan program ini adalah masalah jaringan dan sosialiasi yang perlu ditingkatkan lagi. Kata Kunci : Covid-19, Pelayanan, Administrasi Kependudukan, Si Nduk